1993
DOI: 10.1177/030006059302100202
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Crossover Study of Two Cyclobenzaprine Regimens in Primary Fibromyalgia Syndrome

Abstract: In a double-blind crossover study, the efficacy and tolerability of oral cyclobenzaprine administered in two different regimens were compared in 40 patients affected by primary fibromyalgia syndrome. The patients were randomly divided into two groups. Each group of 20 patients was treated for 15 days with either a single dose of 10 mg/day cyclobenzaprine at bedtime or 30 mg/day cyclobenzaprine in three equal doses daily. Following treatment there was a 15-day washout period before the groups were crossed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…Of these patients, 70 (92%) completed the program. Of the 6 patients who terminated treatment prematurely, 3 reported they were dissatisfied with the program, one reported exacerbation of pain, and no clear reasons were cited by two. Of the 70 patients who completed the treatment program, 3 were excluded from the analyses due to missing data; thus, the present study included 67 FMS patients.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these patients, 70 (92%) completed the program. Of the 6 patients who terminated treatment prematurely, 3 reported they were dissatisfied with the program, one reported exacerbation of pain, and no clear reasons were cited by two. Of the 70 patients who completed the treatment program, 3 were excluded from the analyses due to missing data; thus, the present study included 67 FMS patients.…”
Section: Subjectsmentioning
confidence: 99%
“…The program was an outpatient group rehabilitation program that consisted of 6 one-half-day sessions, spaced over a period of 4 weeks. Groups of [4][5][6][7] patients attended the program 3 times a week during the first week and once a week for the next 3 weeks.…”
Section: Locke-wallace Marital Adjustment Scale (L Wmas)mentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclobenzaprine is chemically close to amitriptyline although it is used as a muscle relaxant with no expected antidepressant effects. The use of cyclobenzaprine resulted in improvement in pain, sleep and fatigue in FM patients [25,26]. Recently, a multi-centered Phase II trial evaluating a small dose sublingual cyclobenzaprine for 12 weeks [27] showed promising benefit for FM and sleep symptoms relative to placebo.…”
Section: Early Studiesmentioning
confidence: 99%